Training And Guidance Of Class Action Research To Improve Professionalism For Primary School Teachers - Prananda, Gingga; Prihantini, Prihantini; Kadiyo, Kadiyo; Rukmini , Ai; Maq , Mumu Muzayyin; Efendi, Nofriza; Oktira , Yona Syaida (Universitas Pahlawan Tuanku Tambusai, 2023)
A research proposal is a description, comprising the steps that will be carried out by the researcher to conduct the research. A research proposal contains problem components, theoretical basis and hypothesis submission, and research methods. The general aim of this activity is to increase teachers' understanding and ability in compiling classroom action research to increase a teacher's professionalism. Participants in this activity came from 25 elementary school teachers. In the presentation of the material presented by the presenter, he provided direction and strategies, as well as equipping the participants with information about how to prepare PTK proposals in this era of independent learning, of course combined with direct experience which the presenter had experienced so that it was more realistic and easier for the seminar participants to understand. This seminar activity was mostly filled with discussions with the participants in determining and formulating an introduction to the PTK process. In general, participants actually know about PTK. The participants were very enthusiastic about taking part in this activity, the seminar went smoothly without any obstacles. The seminar process was fun and certainly memorable for the participants